(untitled) (Biological Sciences - PJSIR, 2008)
. Four medicinal plants namely; Vernonia amygdalina, Psidium guajava, Chromolaena odorata and Anarcadium occidentale, commonly used for the treatment of diarrhoea in Bini traditional folk medicine in Nigeria were tested against Escherichia coli, Staphylococcus aureus and Klebsiella aerogenes. The leaf extracts of P. guajava and A. occidentale completely inhibited the growth of all the organisms tested, while V. amygdalina inhibited the growth of K. aerogenes only. Metronidazole was used as the standard antidiarrhoeal drug. Glycosides were found in all the plant extracts. This study, favours the use of the leaf extracts of A. occidentale, P. guajava and V. amygdalina for the treatment of diarrhoea in Nigeria.